Investigation of cattle manure gasification in a downdraft gasifier using aspen plus - ÖZVEREN, UĞUR (My University, 2022)
Although the Aspen Plus process simulator is widely used to model biomass gasification processes, to our best knowledge, no study has yet been reported for the cattle manure downdraft gasification process. This study presents downdraft gasification characteristics of the cattle manure by performing sensitivity analysis in the Aspen Plus process simulator. Effects of gasifier temperature (between 600-1000 °C) and steam/biomass ratio (between 0.5-2.0) on syngas composition and syngas lower heating value (LHV) were discussed. Sensitivity analysis results indicated the higher ratios of steam/biomass and gasifier temperature of 750 °C are the optimum conditions to produce H2-rich syngas (more than 50% on dry basis). On the other hand, high gasification temperatures and low steam/biomass ratios should be preferred in order to obtain syngas with high calorific value.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG)